1995
DOI: 10.1136/adc.73.2.184-a
|View full text |Cite
|
Sign up to set email alerts
|

Minoxidil induced hair growth after leukaemia treatment?

Abstract: Archives ofDisease in Childhood 1995; 73: 184 for those at the extremes of the normal range for fat/thin, short/tall, clever/stupid, clumsy/ agile, white/black individuals? My own puberty was late. Not much fun at the time but the resultant temporary exclusion from full membership of the peer group has produced a useful long term lesson in coping with the natural ups and downs of life. Explanation, empathy, and reassurance are in my view better medicine in this area, as in many others, than use of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…reported the case of a 4-year-old child with diffuse alopecia that persisted for 14 months following chemotherapy and radiation who subsequently regrew "an almost normal head of hair" after a 9-month course of 2% topical minoxidil daily. 30 There is a paucity of literature investigating oral minoxidil as a treatment for pCIA or pRIA in both adults and children. A single case report describes a 39-year-old woman with pCIA after treatment of acute myeloid leukemia who had a cosmetically significant response to continuous oral minoxidil treatment.…”
Section: Minoxidilmentioning
confidence: 99%
See 1 more Smart Citation
“…reported the case of a 4-year-old child with diffuse alopecia that persisted for 14 months following chemotherapy and radiation who subsequently regrew "an almost normal head of hair" after a 9-month course of 2% topical minoxidil daily. 30 There is a paucity of literature investigating oral minoxidil as a treatment for pCIA or pRIA in both adults and children. A single case report describes a 39-year-old woman with pCIA after treatment of acute myeloid leukemia who had a cosmetically significant response to continuous oral minoxidil treatment.…”
Section: Minoxidilmentioning
confidence: 99%
“…In another cohort of children and adults diagnosed with central nervous system tumor or head and neck sarcoma who were treated with cranial radiotherapy resulting in pRIA, 82% of patients treated with 5% topical minoxidil noted improvement in alopecia 18 . Vickers et al reported the case of a 4‐year‐old child with diffuse alopecia that persisted for 14 months following chemotherapy and radiation who subsequently regrew “an almost normal head of hair” after a 9‐month course of 2% topical minoxidil daily 30 …”
Section: Treatmentmentioning
confidence: 99%